The Good, Bad and Ugly of Plastics. Review of Consumed: How Big Brands Got Us Hooked On Plastic by Saabira Chaudhuri - Venkatesh, G (Studia Ecologiae et Bioethicae, 2026)
The title of this review of Consumed: How Big Brands Got Us Hooked On Plastic, written by Saabira Chaudhuri (her first book) and published by Blink Publishing (an imprint of Bonnier Books UK) in May 2025, is borrowed from writer Mike Berners-Lee’s description of the same. It is a four-part, 13-chapter (all cleverly-titled), 400-page ‘polemic, investigative, change-agent’ which seamlessly blends science, history and story-telling, while availing of well-timed humour which is sure to make readers chuckle quite instinctively. The resort to humour is not to make light of things expedient, but rather to mock at the throwaway consumerism (plastics being one of the enablers for the same) and avaricious profit-seeking which has engulfed not just the western world, but more conspicuously of late, the developing countries as well. Plastics, in a way, have been intricately intertwined with the aforesaid undesirables, which have wrecked havoc on the environment. An ‘alarming’, ‘unputdownable’, ‘gripping’, ‘eye-popping’, ‘honest’, ‘truthful’, ‘deeply-researched’, ‘comprehensive’ must-read (qualifiers adopted by a host of critics and authors to describe Chaudhuri’s book), Consumed, which focuses primarily on the USA, with brief detours to Europe and India, is a valuable addition to the long list of books which have followed Rachel Carson’s Silent Spring. Readers are introduced to many ‘colourful’ interesting characters in the pro-plastics and anti-plastics camps, in this saga. This review takes the reader on a breezy journey through the book, hopefully motivating him/her/them to purchase a copy and be an agent of desirable change, willing to challenge undesirable status quos one after the other. Human behaviour is plastic, and can and should be moulded to answer the call of the century (or rather, the decade, as we do not have the luxury of time on our hands).